(untitled) (Veterinary Science, 2018)
Cystic echinococcosis is endemic in the Rio Negro province of Argentina. After 30 years of control using praziquantel in dogs, the transmission rate to humans and sheep has decreased significantly, however transmission persists The objective of the study is to assess the impact of the inclusion of the EG95 vaccine in sheep in the control program. The vaccine was applied to lambs from communities of native peoples which included 70 producers (Anecón Grande, Mamuel Choique, Nahuel Pan y Río Chico Abajo). From 2009 on, lambs received two doses of the EG95 vaccine when they were 30 and 60 days of age, followed by a single booster injection when the animals were 1 year of age. The transmission of Echinococcus granulosus was assessed through necropsy in mature sheep, Arecoline test and coproantigen test in dogs and register of new clinical cases in inhabitants of the area. A total of 29.323 doses of EG95 vaccine were applied to lambs in the 2009-2017 period, working with 4 groups of 2 veterinaries each, covering 83.5% with one doses, 80.1% with two doses and 85.7% with three doses. Before the vaccine was introduced, in necropsy of sheep of 6 years old showed that 45.7% were infected with E. granulosus. The rate decreased to 21.1% in 2006. The number of cysts per animal decreased from 1.4% to 0.3. The number of producers with infected animals decreased from 84.2% to 22.2%. The humoral response to the vaccination, in field conditions, showed an increased in antibodies with the second dose, reaching its maximum after the booster at one year of age for many years and keeping constant. In dogs, 4.7% was found positive using arecoline purgation and 20.3% of the farms were infected using coproantigen test. The impact assessment showed a 5.6% of dogs positive to the arecoline test. Only a new case of echinococcosis was detected in kids with a 10 cm cyst, and its origin was probably before the vaccination. EG95 vaccine has been effective to prevent the infection in ovines up to six years of age, in spite of the difficulties of achieving better coverage. The transmission to dogs and human beings has to be determined.